Mezi výchovou, vědou, úřadem i řeholí. Život a dílo Jaroslava Schallera a jeho místo v české topografii a řádové historiografii - Václav Bartůšek (Studia Historica Brunensia, 2021)
The study deals in detail with the youth of Jaroslav Schaller and his years of study, especially at the novitiate in Lipník nad Bečvou and his private studies in the Piarist order. The author follows Schaller's work, particularly his sixteen-part Topographie des Königreiches Böhmen and the description of the capital city of Prague Beschreibung der königlichen Haupt- und Residenzstadt Prag. He also focuses on his further life and work, a significant encyclopedia on the history of pedagogy of the Piarist order, the original findings of which were already to be found in Schaller's topographic writings, and another book on pedagogy and the educational efforts of the Piarist order.